Structural fatigue investigation of transverse surface crack growth in rail steels and thermite welds subjected to in-plane and out-of-plane loading. (1st February 2020) - Liu, Yang; Tsang, Kin Shun; Hoh, Hsin Jen; Shi, Xiaopeng; Pang, John Hock Lye
Highlights: Stress intensity factors were derived for transverse surface cracks in rail and welds. Fracture and fatigue properties of thermite weld material were determined. A fatigue crack growth prediction algorithm was developed. Out-of-plane bending was found to more critical than in-plane bending. Abstract: This study investigates the structural fatigue crack growth behavior of observed transverse surface cracks in rail steel and thermite weld subjected to in-plane and out-of-plane loading. Stress Intensity Factor (SIFs) solutions were derived from finite element model analysis for transverse surface cracks located at five different crack initiation locations in the cross-section of rail steel and thermite weld. The SIFs were presented by the conventional geometry factor Y and weld magnification factor M k solutions for rail steel and thermite weld. Fracture toughness and fatigue crack growth rate tests were conducted to determine the mechanical properties of thermite weld materials and are compared with reported data for rail steels (R260 and R350HT). Fatigue crack growth prediction algorithm was developed using the coupled root mean square integration approach and was compared with the conventional uncoupled two-degree of freedom approach for semi-elliptical surface crack growth in the depth and surface directions respectively. The fatigue crack growth algorithm and propagation life prediction provide valuable observations on the crack shape evolution. It proves that out-of-plane bending loading is a more significant failure mode as compared to in-plane bending loading for thermite weld joints at curve tracks. Fatigue crack propagation results provide fatigue stress range-life curves for weld-toe surface cracks initiated at the head-to-web region of thermite welded joint structure.